Aspects of improving employee performance - Wiedya Riski Purnamasari; Roni Kambaraa; Didit Haryadi (Institute of Computer Science (IOCS), 2023)
Management can achieve success if the resources are owned, Management can only succeed if it has resources, especially human resources. Employees are therefore a key factor in making a real contribution to the sustainable success of the organization. Therefore, only optimally performing employees can achieve this success. Therefore, various aspects need to be improved to maximize employee performance. This study aims to analyze how these aspects can improve employee performance. This research uses an associative quantitative approach based on PLS-SEM. The results show that training effectiveness has a positive impact on organizational commitment and a significant positive impact on employee performance. However, training effectiveness does not affect employee performance. However, organizational commitment indirectly and optimally can be a driving force to improve employee performance.